The Rendu-Osler-Weber Disease Revealed by a Refractory Hypoxemia and Severe Cerebral Fat Embolism - Leonel Barreto; Jean-Bernard Amiel; Anthony Dugard; Nicolas Pichon; Marc Clavel; Bruno François; Philippe Vignon (Case Reports in Critical Care)
The Rendu-Osler-Weber disease is a genetic disease which may lead to severe hemorrhage and less frequently to severe organ dysfunction. We report the case of a 22-year-old patient with no personal medical history who was involved in a motorcycle accident and exhibited severe complications related to large arteriovenous pulmonary shunts during his ICU stay. The patient developed an unexplained severe hypoxemia which was attributed to several arteriovenous shunts of the pulmonary vasculature by a contrast study during a transesophageal echocardiographic examination. The course was subsequently complicated by a prolonged coma associated with hemiplegia which was attributed to a massive paradoxical fat embolism in the setting of an untreated femoral fracture. In addition to hemorrhagic complications which may lead to intractable shock, arteriovenous malformations associated with the Rendu-Osler-Weber disease may involve the pulmonary vasculature and result in unexpected complications, such as hypoxemia or severe cerebral fat embolism in high-risk patients.